Keadilan Pajak dalam Perspektif Hukum dan Etika Sosial - Dian Alex Candra (Institut Nalanda, 2026)
Tax justice is a fundamental principle in modern fiscal systems, closely related to legal frameworks and social ethics. This study examines tax justice from both legal and socio-ethical perspectives, emphasizing its role in ensuring equitable distribution of fiscal burdens and promoting public trust in government institutions. The objective of this research is to analyze how tax policies reflect principles of fairness and how ethical considerations influence compliance and enforcement. The study employs a qualitative normative approach by reviewing legal regulations, academic literature, and comparative tax practices. The findings indicate that tax justice is not solely determined by statutory provisions but also by the perception of fairness among taxpayers. Inequities in tax implementation, such as unequal enforcement and regressive structures, can undermine compliance and social cohesion. Furthermore, ethical dimensions such as transparency, accountability, and solidarity play a crucial role in strengthening voluntary compliance. The study concludes that achieving tax justice requires an integrated approach combining robust legal frameworks with ethical governance practices.